Assessment of growth monitoring and activities related to the growth promotion of children aged one to three years in Colombo Municiple Council area. - Wijayathilaka, H.V.B.S (My University, 2002)
The main objective is to determine factors influencing growth monitoring.to assess groth promotional activities and the skills of mothers in interpriting growth curves in CHDR and also to determine the service factors for growth monitoring provided by the CMC.The study revealed 99 person of the children possessed CHDR.85 person of the childrenof the study area attend to CWC in the CMC.Knowledge of mother on Frequancy of weighting,has significantly improved the weighting of the children.Dropouts have significantly reduced when the birth space from the immediate younger sibling is less than one year.Fathers lacking school education have significant adverse effect on the weghting of the children.The type of clinic atrtending has not shown effect on the frequancy of weighting.